Thermally conductive, flame retardant polycarbonate composition having a high comparative tracking index
By combining graphite with aromatic polyacylates and adding a fire anti-removing agent with phosphorus content, a thermally conductive polyacylate material with high CTI and fire anti-removing performance was prepared, which solved the problem of insufficient performance of materials in high-temperature applications in the prior art, and achieved multiple performance improvements of the materials.
Patent Information
- Application Number
- JP2024560589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-06
- Publication Date
- 2025-04-16
AI Technical Summary
The prior art is difficult to provide thermally conductive polyacylate materials with high comparative tracking index (CTI) and good fire de-reduction properties for electronic and electrical (EE) components in high temperature applications.
A thermally conductive polyacylate material with high CTI and fire prevention and fire prevention properties was prepared by combining graphite (talc) with aromatic polyacylates and adding phosphorus content fire prevention and polyacylates, anti-drip agents and polyacylates of specific unit structures.
It has achieved the improvement of polyacylate materials in high CTI and fire prevention and deterioration performance, while maintaining good thermal conductivity and thermal deformation performance, and is suitable for high-temperature electronic and electrical components.
Smart Images

Figure 2025512096000001 
Figure 2025512096000002 
Figure 2025512096000003
Abstract
Description
[Technical field]
[0001] The present invention relates to thermally conductive, flame retardant thermoplastic compositions based on polycarbonate having a high comparative tracking index. [Background technology]
[0002] Polycarbonate offers many advantages over other thermoplastic polymers due to its high impact strength, high heat distortion resistance, and certain inherent flame retardancy. Due to this unique property profile, polycarbonate compositions are in principle suitable for a wide variety of applications, for example in the field of electrical and electronic components. In particular, good insulating properties and high flame retardancy are essential safety-related basic requirements for materials used in this field.
[0003] In applications where plastics are in direct contact with conductor tracks, a high resistance to tracking currents under voltage load is a prerequisite to ensure that there are no short circuits in the component and therefore no fires. Comparative Tracking Index (CTI) generally describes the resistance of plastic materials to environmental influences. The CTI value is a measure of the tendency of plastics to form conductive paths on the surface under voltage and promote the generation of electrical tracking currents under the influence of environmental influences, such as moisture and pollution. The higher the tracking current resistance of a material, i.e. the higher its Comparative Tracking Index (CTI value), the better it is suitable for use in high voltage applications, such as modern electromobility applications. Another advantage of materials with high CTI values is that it is possible to place conductor tracks close together in electronic components without risk of short circuits, which in turn allows for a reduction in component dimensions and therefore a more compact design and weight reduction.
[0004] In contrast to other thermoplastic polymers, such as polystyrene, polyesters, etc., polycarbonate has a very low comparative tracking index and a moderate flame retardancy by itself. Due to the high proportion of aromatic structures, polycarbonate has a relatively high tendency to char. The CTI of pure polycarbonate is about 250 V or even lower (Non-Patent Document 1). However, for many applications in the electronic / electrical (EE) sector, such as the electromobility sector, for safety reasons, the materials used are required to have a higher CTI, for example at least 375 V, preferably at least 400 V (corresponding to insulating material group PLC 0 according to EN 50124). Therefore, polycarbonate has not been considered so far as a material for many applications that particularly require a high comparative tracking index of the material.
[0005] For applications requiring a high comparative tracking index of the material, the material must simultaneously have high flame retardancy, i.e. classification V0 according to UL 94V, even at particularly low wall thicknesses.
[0006] Pure polycarbonate typically already has a certain inherent flame retardancy (classification V2 according to UL94V), which is insufficient for most applications in the EE sector. In order to achieve the required classification V0 according to UL94V, the addition of suitable flame retardants is required. Typically employed in polycarbonates are halogenated sulfonic acid compounds (e.g. Rimar salts (potassium perfluorobutanesulfonate, C4 salts) or KSS salts (potassium diphenylsulfone-3-sulfonate)), or also organophosphate compounds (e.g. bisphenol A bis(diphenylphosphate) (BDP), resorcinol bis(diphenylphosphate) (RDP)), or phosphazenes. The flame retardancy of polycarbonate can in principle be very well adjusted by adding suitable flame retardant additives. However, the mechanism of action of such flame retardants is based on the formation of a solid charred surface layer that blocks the oxygen supply and thus inhibits the combustion process.
[0007] However, the effect that forms the basis of a good comparative tracking index is, inter alia, a low tendency to form conductive paths on the surface, which is the exact opposite of the "charring" mechanism of action of surfactant flame retardants and therefore poses a special challenge in achieving a high comparative tracking index and good flame retardancy in polycarbonate materials.
[0008] In the field of electronic or current-carrying components, there is a particular need for materials with a high comparative tracking index. Every current flow is accompanied by the generation of heat, which increases with increasing power. To ensure the life of such components by preventing technical failures, it is necessary to dissipate the generated heat sufficiently. It would be desirable to be able to provide polycarbonate materials that have a relatively high comparative tracking index and flame retardancy, and at the same time can also contribute to the dissipation of heat.
[0009] Thermally conductive polycarbonate materials are known in principle from the prior art. For example, US Pat. No. 5,399,433 describes corresponding compositions in which the thermal conductivity is improved by the use of talc. The basic polymer degradation caused by talc is largely suppressed by the addition of maleic anhydride modified olefin waxes, resulting in materials with advantageous mechanical properties. However, such materials do not have good flame retardancy, nor do the comparative tracking indices increase significantly compared to pure polycarbonate.
[0010] The aim was therefore to provide a thermally conductive polycarbonate-based composition which achieves UL94 classification V0 at 2 mm, preferably at 1.5 mm, and which preferably has a high CTI of at least 375 V, preferably at least 400 V, as specified according to the rapid test method according to IEC 60112:2009. The thermal conductivity (in-plane) is preferably at least 0.9 W / (mK), as specified according to ASTM E 1461-13. Due to the field of application and the heat development in EE parts, the composition should also preferably have a good heat distortion resistance, in particular a Vicat softening temperature, as specified according to ISO 306:2014-3, VST method B, of at least 107°C, preferably at least 108°C, particularly preferably at least 120°C.
[0011] Surprisingly, it has been found that this objective of providing a composition having such a complex property profile is achieved by the combination of talc and aromatic polycarbonate with a phosphorus-containing flame retardant, with an anti-drip agent, and by the use of polycarbonates containing specific monomer units, each in selected amount ranges. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] International Publication No. 2018 / 037037 [Non-patent literature]
[0013] [Non-Patent Document 1] F. Acquasanta et al., Polymer Degradation and Stability, 96 (2011), 2098-2103 Summary of the Invention [Problem to be solved by the invention]
[0014] Accordingly, the present invention provides a thermoplastic composition, the composition comprising: A) at least 44.5% by weight of an aromatic polycarbonate; Here, the aromatic polycarbonate is Contains one or more monomer units of formula (1a) in a proportion of 30% by weight to 65% by weight based on the total weight of the aromatic polycarbonate; TIFF2025512096000001.tif44170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, R 2 is a C1-C4-alkyl radical, n is 0, 1, 2, or 3; B) 30% to 40% by weight of talc; C) 6% by weight to 14% by weight of a phosphorus-containing flame retardant; where the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3% by weight to 2.0% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; Contains When the talc content is less than 35.0% by weight, the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight; When the talc content is greater than 37% by weight, the phosphazene is present as a phosphorus-containing flame retardant and the phosphazene content is greater than 10.0% by weight.
[0015] In addition to components A, B, C, D and E, the composition according to the invention may contain further components, for example further additives, in the form of component F. The composition may also contain one or more further thermoplastics not included in any of components A to F as blend partners (component G). In the context of the present invention, unless expressly specified otherwise, the weight percentage values specified for components A, B, C, D, E and optionally F, and also optionally blend partners, respectively, are based on the total weight of the composition. It will be understood that all components present in the composition according to the invention add up to 100% by weight. When a numerical range has an upper limit indicated by "~X", this includes the specified numerical value and its upward rounding range.
[0016] Thermoplastic polymers suitable as blend partners apart from components A and E include, for example, polystyrene, styrene copolymers, aromatic polyesters such as polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), PET-cyclohexanedimethanol copolymers (PETG), polyethylene naphthalate (PEN), PMMA and PMMA copolymers, and copolymers with styrene, such as transparent polystyrene-acrylonitrile (PSAN), or else also thermoplastic polyurethanes. Such blend partners are preferably used in concentrations of 0.5% to 10% by weight.
[0017] However, it is especially preferred when the above compositions do not contain any additional components, but instead the amounts of component A, component B, component C, component D, component E and optionally component F, in particular in the preferred embodiments described, total 100% by weight, i.e. the composition according to the invention consists of component A, component B, component C, component D, component E and optionally component F.
[0018] It is understood that the components used may contain typical impurities, such as impurities resulting from their manufacturing process. It is preferable to use components with the highest possible purity. Moreover, it is understood that such impurities may be present even in the event of comprehensive formulation of the composition.
[0019] The compositions according to the invention do not show any significant tracking current (more than 0.5 A for 2 seconds) even when subjected to at least 50 drops of a 0.1% ammonium chloride solution at 375 V, more preferably at 400 V and especially preferably at 500 V, preferably according to the rapid test method according to IEC 60112:2009 and described in the description section. Preferably, the compositions according to the invention have a flame retardancy according to UL 94 V of V0 for a specimen thickness of 3 mm, more preferably at least V1 and especially preferably V0 for a specimen thickness of 2 mm, in each case after the specimens have been conditioned for 7 days at 50% relative humidity and 70° C. ambient temperature. In addition to a high CTI and good flame retardancy, the composition preferably also has good heat distortion resistance, which is expressed in terms of a Vicat softening temperature, as determined according to ISO 306:2014-3, VST method B, of at least 107°C, preferably at least 108°C, particularly preferably at least 120°C.
[0020] The individual components of the composition according to the invention are described in more detail hereinafter:
[0021] Ingredient A Component A of the composition according to the invention is an aromatic polycarbonate.
[0022] Aromatic polycarbonates in the context of the present invention include not only homopolycarbonates but also copolycarbonates and / or polyestercarbonates. The polycarbonates can be linear or branched in a known manner. Polycarbonate mixtures can also be used according to the present invention.
[0023] The thermoplastic polycarbonates, including thermoplastic aromatic polyester carbonates, preferably have a weight average molecular weight M w is 15000 g / mol to 40000 g / mol, more preferably 34000 g / mol, particularly preferably 17000 g / mol to 33000 g / mol, and particularly preferably 19000 g / mol to 32000 g / mol; w is determined by gel permeation chromatography using dichloromethane as eluent and calibrated against bisphenol A polycarbonate standards, using linear polycarbonate (formed from bisphenol A and phosgene) of known molar mass distribution from PSS Polymer Standards Service GmbH, Germany, using calibration according to method 2301-0257502-09D (2009 German edition) from Currenta GmbH & Co. OHG, Leverkusen. The eluent is dichloromethane. The column combination is a crosslinked styrene-divinylbenzene resin. Analytical column diameter: 7.5 mm; length: 300 mm. Column material particle size: 3 μm-20 μm. Solution concentration: 0.2 wt.%. Flow rate: 1.0 ml / min, solution temperature: 30°C. UV and / or RI detection is used.
[0024] The melt volume flow rate (MVR) of the aromatic polycarbonate used is specified according to ISO 1133:2012-03 at a test temperature of 300°C and a load of 1.2 kg, preferably at 5 cm 3 / (10 minutes)~35cm 3 / (10 min), more preferably 6 cm 3 / (10 minutes)~25cm 3 / (10 min), and even more preferably 6 cm 3 / (10 minutes)~21cm 3 / (10 minutes).
[0025] A maximum of 80 mol %, preferably 20 mol % to 50 mol %, of the carbonate groups of the polycarbonates used according to the invention can be replaced by aromatic dicarboxylic acid ester groups. Polycarbonates of this type, in which acid radicals derived from aromatic dicarboxylic acids as well as from carbonic acid are introduced into the molecular chain, are called aromatic polyester carbonates. For the purposes of the present invention, they are encompassed by the general term "thermoplastic aromatic polycarbonates".
[0026] The details of polycarbonate preparation have been described in numerous patent specifications over the past 40 years or so. In this specification, the following may be mentioned by way of example: Schnell, "Chemistry and Physics of Polycarbonates", Polymer Reviews, Volume 9, Interscience Publishers, New York, London, Sydney 1964, D. Freitag, U. Grigo, PR Mueller, H. Nouvertne, BAYER AG, "Polycarbonates" in Encyclopedia of Polymer Science and Engineering, Volume 11, Second Edition, 1988, pages 648-718, and finally U. Grigo, K. Kirchner and PR Mueller "Polycarbonate" [Polycarbonates] in Becker / Braun, Kunststoff-Handbuch [Plastics Handbook], volume 3 / 1, Polycarbonate, Polyacetale, Polyester, Celluloseester [Polycarbonates, Polyacetals, Polyesters, Cellulose Esters], Carl Hanser Verlag Munich, Vienna 1992, pages 117 to 299.
[0027] Aromatic polycarbonates are prepared, for example, by the interfacial process, by reaction of dihydroxyaryl compounds with carbonyl halides, preferably phosgene, and / or aromatic dicarbonyl dihalides, preferably benzene dicarbonyl dihalides, optionally using chain terminators and optionally using trifunctional or higher branching agents. Also possible is the preparation by reaction of dihydroxyaryl compounds with, for example, diphenyl carbonate, via melt polymerization methods.
[0028] For the preparation of polyester carbonates, a portion of the carbonic acid derivatives is replaced with aromatic dicarboxylic acids or dicarboxylic acid derivatives, specifically aromatic dicarboxylic ester structural units according to the carbonate structural units to be replaced in the aromatic polycarbonate.
[0029] Dihydroxyaryl compounds suitable for the preparation of polycarbonates are of formula (1) HO-Z-OH (1), During the ceremony, Z is an aromatic radical having 6 to 30 carbon atoms, which may have one or more aromatic rings, which may be substituted, and which may have aliphatic or alicyclic radicals or alkylaryl or heteroatoms as bridging elements.
[0030] Suitably, Z in formula (1) is a radical of formula (2): TIFF2025512096000002.tif27170 formula, R 6 and R 7 are independently H, C1 to C 18 -Alkyl, C1-C 18 -alkoxy, halogen such as Cl or Br, or, in each case, optionally substituted aryl or aralkyl, preferably H or C1-C 12 -alkyl, particularly preferably H or C1-C8-alkyl, especially preferably H or methyl, X is a single bond, -SO2-, -CO-, -O-, -S-, C1-C6-alkylene, C2-C5-alkylidene or C5-C6-cycloalkylidene, which can be substituted by C1-C6-alkyl, preferably methyl or ethyl, or C6-C 12 -arylene, which may be optionally fused to a further aromatic ring containing a heteroatom.
[0031] X is preferably a single bond, C1-C5-alkylene, C2-C5-alkylidene, C5-C6-cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2- or a radical of formula (3). TIFF2025512096000003.tif28170
[0032] Examples of dihydroxyaryl compounds include: dihydroxybenzene, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)aryls, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl)sulfones, bis(hydroxyphenyl)sulfoxides, 1,1'-bis(hydroxyphenyl)diisopropylbenzene, and their ring-alkylated and ring-halogenated compounds.
[0033] Dihydroxyaryl compounds suitable for the preparation of polycarbonates include, for example, hydroquinone, resorcinol, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfones, bis(hydroxyphenyl)sulfoxides, α,α'-bis(hydroxyphenyl)diisopropylbenzene, phthalimidines derived from isatin or phenolphthalein derivatives, and their ring-alkylated, ring-arylated, and ring-halogenated compounds.
[0034] Suitable dihydroxyaryl compounds are 4,4'-dihydroxydiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)-p-diisopropylbenzene, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, dimethylbisphenol A, bis(3,5-dimethyl-4-hydroxyphenyl)methane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4-hydroxyphenyl)sulfone, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-p-diisopropylbenzene, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, as well as the following dihydroxyaryl compounds (I) to (III): TIFF2025512096000004.tif46170, in which each R' is a C1-C4-alkyl radical, an aralkyl radical or an aryl radical, preferably a methyl radical or a phenyl radical, particularly preferably a methyl radical.
[0035] Particularly preferred dihydroxyaryl compounds are 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxydiphenyl, and dimethylbisphenol A, as well as bisphenols of formulae (I), (II), and (III).
[0036] These and other suitable dihydroxyaryl compounds are described, for example, in U.S. Pat. Nos. 3,028,635, 2,999,835, 3,148,172, 2,991,273, 3,271,367, 4,982,014 and 2,999,846, in DE-A-1,570,703, DE-A-2,063,050, DE-A-2,036,052, DE-A-2,211,956 and DE-A-3,832,396, in FR-A-1,561,518 and in the research article "H. Schnell, Chemistry and Physics of Polycarbonates, Interscience Publishers, New York, 1989, 1991, and 1998. 1964", as well as in JP-A-1986-62039, JP-A-1986-62040, and JP-A-1986-105550.
[0037] In the case of homopolycarbonates, only one type of dihydroxyaryl compound is used, whereas in the case of copolycarbonates, two or more types of dihydroxyaryl compounds are used.
[0038] Examples of suitable carbonic acid derivatives include phosgene or diphenyl carbonate.
[0039] Suitable chain terminators that can be used in the preparation of the polycarbonates are monophenols. Examples of suitable monophenols include phenol itself, alkylphenols such as cresol, p-tert-butylphenol, cumylphenol, and mixtures thereof.
[0040] Suitable chain terminators include one or more linear or branched, preferably unsubstituted, C1-C 30 -alkyl radical- or tert-butyl-substituted phenol. Particularly suitable chain terminators are phenol, cumylphenol, and / or p-tert-butylphenol.
[0041] The amount of chain terminator used is preferably 0.1 mol% to 5 mol%, based on the moles of dihydroxyaryl compound used in each case. The chain terminator can be added before, during or after the reaction with the carbonic acid derivative.
[0042] Suitable branching agents are trifunctional or higher compounds known in polycarbonate chemistry, especially those having three or more phenolic OH groups.
[0043] Examples of suitable branching agents include 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, 2,6-bis(2-hydroxy-5'-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-hydroxyphenyl)methane, tetra(4-(4-hydroxyphenylisopropyl)phenoxy)methane, and 1,4-bis((4',4''-dihydroxytriphenyl)methyl)benzene, and 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole.
[0044] Whatever branching agent is used, its amount is preferably between 0.05 mol % and 2.00 mol %, based on the moles of dihydroxyaryl compound used in each case.
[0045] The branching agent can either form the first charge with the dihydroxyaryl compound and the chain terminator in the aqueous alkaline phase or be added dissolved in an organic solvent prior to phosgenation. In the case of the transesterification process, the branching agent is used together with the dihydroxyaryl compound.
[0046] Particularly suitable polycarbonates are homopolycarbonates based on bisphenol A, homopolycarbonates based on 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and copolycarbonates based on the two monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane or based on the two monomers bisphenol A and 4,4'-dihydroxydiphenyl, as well as polycarbonates of formula (I), (II) and / or (III): TIFF2025512096000005.tif48170, where each R' is C1-C4-alkyl, aralkyl or aryl, preferably methyl or phenyl, especially preferably methyl, and in particular homo- or copolycarbonates derived from bisphenol A. Particularly preferred aromatic polycarbonates include bisphenol A-based homopolycarbonates and copolycarbonates based on the two monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane. Very preferably, the aromatic polycarbonate is a mixture of bisphenol A-based homopolycarbonates and copolycarbonates based on the two monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane.
[0047] The total proportion of monomer units based on the formulae (I), (II), (III), 4,4'-dihydroxydiphenyl and / or bisphenol TMC in the copolycarbonate is preferably 0.1 mol % to 88 mol %, particularly preferably 1 mol % to 86 mol %, especially preferably 5 mol % to 84 mol % and in particular 10 mol % to 82 mol % (based on the sum of the moles of the dihydroxyaryl compounds used).
[0048] The relative solution viscosity of the copolycarbonates, as specified according to ISO 1628-4:1999, is preferably in the range of 1.15 to 1.35.
[0049] The dihydroxyaryl compounds used, as well as all other chemicals and auxiliaries added in the synthesis, may be contaminated with impurities from their own synthesis, handling, and storage, however, it is desirable to use raw materials with the highest possible purity.
[0050] Examples of aromatic dicarboxylic acids suitable for the preparation of polyester carbonates include orthophthalic acid, terephthalic acid, isophthalic acid, tert-butylisophthalic acid, 3,3'-diphenyldicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4-benzophenonedicarboxylic acid, 3,4'-benzophenonedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 2,2-bis(4-carboxyphenyl)propane, trimethyl-3-phenylindane-4,5'-dicarboxylic acid.
[0051] Among the aromatic dicarboxylic acids, particular preference is given to the use of terephthalic acid and / or isophthalic acid.
[0052] Derivatives of dicarboxylic acids include dicarbonyl dihalides and dialkyl dicarboxylates, especially dicarbonyl dichloride and dimethyl dicarboxylate.
[0053] The replacement of carbonate groups with aromatic dicarboxylic acid ester groups is substantially stoichiometric and quantitative, so that the molar ratios of the reactants are also maintained in the final polyestercarbonate. The aromatic dicarboxylic acid ester groups can be incorporated either randomly or in blocks.
[0054] The composition according to the invention contains at least 44.5% by weight, preferably at least 50% by weight, of aromatic polycarbonate and is therefore based on aromatic polycarbonate.
[0055] According to the invention, the aromatic polycarbonate of the composition contains from 30% to 65% by weight, preferably from 60% by weight, particularly preferably from 40% to 55% by weight, especially preferably from 40% to 50% by weight, of one or more monomer units of formula (1a), based on the total weight of the aromatic polycarbonate, TIFF2025512096000006.tif44170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, preferably hydrogen, R 2 is a C1-C4-alkyl radical, preferably a methyl radical, n is 0, 1, 2 or 3, preferably 3.
[0056] Corresponding copolycarbonates which are preferably used according to the invention are available, for example, under the name "APEC™" from Covestro Deutschland AG.
[0057] The abovementioned contents of the corresponding monomeric units, for example bisphenol TMC, in the aromatic polycarbonates of the composition are achieved by mixing or exclusively using homopolycarbonates composed of such monomeric units, preferably bisphenol TMC homopolycarbonates, with one or more other (co)polycarbonates, or by mixing with copolycarbonates containing the corresponding units, preferably containing bisphenol TMC units, or by mixing with one or more homopolycarbonates or copolycarbonates containing the corresponding monomeric units, preferably containing bisphenol TMC units. According to the invention, the aromatic polycarbonates of the composition are particularly preferably copolycarbonates containing bisphenol TMC units, or mixtures of copolycarbonates containing bisphenol TMC units with bisphenol A homopolycarbonate. "Polycarbonates containing bisphenol TMC units" is understood according to the invention to mean polycarbonates containing bisphenol TMC as incorporated monomeric units.
[0058] The bisphenol TMC 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (formula (1a')) and its use in homopolycarbonates are known from the literature (DE-A 39 18 406). TIFF2025512096000007.tif32170
[0059] The total proportion of monomer units of the formula (1a') in the copolycarbonate is preferably 0.1 mol% to 88 mol%, particularly preferably 1 mol% to 86 mol%, especially preferably 5 mol% to 84 mol% and in particular 10 mol% to 82 mol% (based on the sum of the moles of the diphenols used).
[0060] If the bisphenol TMC content in the copolycarbonate is 30% by weight or more, the Vicat temperature (VST / B 120; ISO 306:2013) of the copolycarbonate is greater than 175° C. Bisphenol A is preferably used as a comonomer. Particularly preferably, the copolycarbonate is formed from the monomers bisphenol TMC and bisphenol A.
[0061] The copolycarbonates may be in the form of block copolycarbonates and random copolycarbonates, with the random copolycarbonates being particularly preferred.
[0062] Component B Talc in the context of the present invention is preferably a talc, or a mixture of talcs, of essentially the same chemical composition, particle size, porosity, and / or BET surface area.
[0063] Talc is a phyllosilicate with the general chemical composition Mg3[SiO 10 It can be described as magnesium silicate hydrate having the general formula [(OH)2]. However, different types of talc may deviate from this general composition as they contain different impurities.
[0064] The talc or talc mixture used for preparing the composition according to the invention may be sized or unsized. The talc is preferably unsized. In the context of the present invention, size is considered to be the controlled (chemisorption or physisorption) concentration of molecules on the surface. Thus, unsized talc is a talc that has not been surface-treated, i.e. after the talc particles with the desired particle size are collected and optionally subjected to compression, the talc is preferably not subjected to any further process steps that change the surface of the talc in a controlled manner by chemisorption and / or physisorption. However, this does not exclude that impurities, dust or similar particles may unintentionally reach part of the surface during further handling of the talc, as long as the surface of the talc does not lose its properties to a significant extent, especially in relation to pH.
[0065] Talc preferably has a pH of 8 to 10, particularly preferably 8.5 to 9.8, especially preferably 9.0 to 9.7, the pH being specified according to EN ISO 787-9:1995. It should be noted that EN ISO 787-9:1995 also refers to the option of adding ethanol or other organic solvents to improve the dispersion of the solid to be analyzed. According to the invention, preference is given to using only distilled water to specify the pH according to EN ISO 787-9:1995.
[0066] The talc component B preferably has a content of iron(II) oxide and / or iron(III) oxide of 0.2% to 2.5% by weight, particularly preferably 0.3% to 2.3% by weight, especially preferably 0.3% to 2.0% by weight. This content is preferably measured by X-ray fluorescence or atomic absorption spectroscopy. The content of iron oxide in the talc influences the degree of decomposition of polycarbonate. It is advantageous to use talc with a specified iron oxide content.
[0067] Component B also preferably has an aluminum oxide content of 0.01% to 0.5% by weight, particularly preferably 0.05% to 0.48% by weight and especially preferably 0.15% to 0.45% by weight.
[0068] Component B preferably has an average particle size D50 of 0.01 μm to 10 μm, particularly preferably 0.25 μm to 10.00 μm, and even more preferably 0.5 μm to 10.00 μm, where the particle size D50 is determined by sedimentation analysis. The average D50 value is understood by the skilled person to mean the average particle size at which 50% of the particles are smaller than the stated value. The particle size D50 is preferably determined according to ISO13317-3:2001.
[0069] Component B is preferably 7.5 m 2 / g~20.0m 2 / g, particularly preferably 9.0m 2 / g~15.0m 2 / g, especially preferably 9.5m 2 / g~14.0m 2 / g. The determination of the surface area according to Brunauer, Emmett and Teller by gas adsorption is known per se to the person skilled in the art. The BET surface area is preferably determined according to ISO 4652:2012. This preferred BET surface area is particularly preferably related to the above-mentioned average particle size D50 of talc. In the case of such a combination, it has been found that the component B used according to the invention is optimally matched to the component C used according to the invention. The specific acid number and molar mass of component E make it possible to minimize the decomposition of the polycarbonate caused by component B.
[0070] Particularly preferably, the talc has a talc content of more than 96% by weight, particularly preferably more than 97% by weight and especially preferably more than 98% by weight.
[0071] Likewise, the talc preferably has an ignition loss of 5.0% to 7.0% by weight, particularly preferably 5.2% to 6.5% by weight, and especially preferably 5.3% to 6.2% by weight at 1050° C. The ignition loss is preferably specified according to DIN 51081:2002.
[0072] The talc or talc mixture according to component B is preferably in compressed form. In the case of a talc mixture, the abovementioned values are based on the entire talc mixture, i.e. component B, respectively.
[0073] The composition according to the present invention has a talc content of 30% to 40% by weight, preferably 30% to 35% by weight, based on the total weight of the composition.
[0074] Component C Component C of the composition according to the invention is a phosphorus-containing flame retardant, which may be a single phosphorus-containing flame retardant or a mixture of different phosphorus-containing flame retardants.
[0075] Suitable phosphorus-containing flame retardants are cyclic phosphazenes, phosphorus compounds of formula (10), and mixtures thereof: TIFF2025512096000008.tif36170 formula, R 1 , R 2 , R 3 , and R 4 are independently a C1-C8-alkyl radical, which in each case is optionally halogenated, in each case branched or unbranched, and / or a C5-C6-cycloalkyl radical, a C6-C 20 -aryl radical, or C7-C 12 - aralkyl radicals, which in each case are optionally substituted by branched or unbranched alkyl and / or halogen, preferably chlorine and / or bromine, n is independently 0 or 1; q is a value between 0 and 30; X is a monocyclic or polycyclic aromatic radical having 6 to 30 carbon atoms, or a straight or branched chain aliphatic radical having 2 to 30 carbon atoms, each of which can be substituted or unsubstituted and bridged or non-bridged.
[0076] Preferably, R 1 , R 2 , R 3 , and R 4 is independently branched or unbranched C1-C4-alkyl, phenyl, naphthyl, or C1-C4-alkyl substituted phenyl. 1 , R 2 , R 3 , and / or R 4 If they are radicals, these in turn can be substituted by halogens and / or alkyl groups, preferably chlorine, bromine and / or branched or unbranched C1-C4-alkyl. Particularly suitable aryl radicals are those corresponding to cresyl, phenyl, xylenyl, propylphenyl or butylphenyl, as well as their brominated and chlorinated derivatives.
[0077] X in formula (10) is preferably derived from a dihydroxyaryl compound.
[0078] X in formula (10) is particularly preferably the following: TIFF2025512096000009.tif59170 or their chlorinated and / or brominated derivatives. X (together with the adjacent oxygen atom) is preferably derived from hydroquinone, bisphenol A or diphenylphenol. It is likewise suitable that X is derived from resorcinol. Particularly preferably, X is derived from bisphenol A. n in formula (10) is preferably equal to 1. q is preferably 0 to 20, particularly preferably 0 to 10, and in the case of mixtures has an average value of 0.8 to 5.0, preferably 1.0 to 3.0, further preferably 1.05 to 2.00, particularly preferably 1.08 to 1.60.
[0079] The phosphorus compound of the general formula (10) is preferably a compound of the formula (11), TIFF2025512096000010.tif40170 formula, R 1 , R 2 , R 3 , and R 4 are each independently a linear or branched C1-C8 alkyl radical and / or optionally a linear or branched alkyl substituted C5-C6 cycloalkyl radical, C6-C 10 -aryl radical, or C7-C 12 -aralkyl radical, n is independently 0 or 1; q is independently 0, 1, 2, 3, or 4; N is a number between 1 and 30, R 5 and R 6 are independently a linear or branched C1-C4-alkyl radical, preferably a methyl radical, Y is a linear or branched C1-C7 alkylidene, linear or branched C1-C7 alkylene radical, C5-C 12 -Cycloalkylene radical, C5-C 12 - a cycloalkylidene radical, -O-, -S-, -SO-, SO2, or -CO-.
[0080] Phosphorus compounds of formula (10) include, in particular, tributyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, 2-ethyl cresyl diphenyl phosphate, tri(isopropylphenyl) phosphate, resorcinol bridged oligophosphate esters, and bisphenol A bridged oligophosphate esters. When phosphorus compounds of formula (10) are used, the use of oligomeric phosphate esters of formula (10) derived from bisphenol A is particularly preferred.
[0081] Further preference is given to the use of mixtures of the same structure but different chain lengths, in which case the q value specified is the average of the q values, determined by determining the composition (molecular weight distribution) of the mixture of phosphorus compounds by high pressure liquid chromatography (HPLC) in a mixture of acetonitrile and water (50:50) at 40°C and using this to calculate the average value of q.
[0082] Particularly preferably, bisphenol A-based oligophosphates according to formula (12) (bisphenol A bis(diphenyl phosphate)) with q=1 to 20, in particular q=1.0 to 1.2, are present in the composition according to the invention. TIFF2025512096000011.tif55170
[0083] Phosphorus compounds of this type are known (see, for example, EP-A-0 363 608, EP-A-0 640 655) or can be prepared in an analogous manner by known methods (see, for example, Ullmanns Enzyklopaedie der technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], vol. 18, p. 301 ff., 1979; Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], vol. 12 / 1, p. 43; Beilstein vol. 6, p. 177).
[0084] Alternatively, it is particularly preferred to use as component C a cyclic phosphazene according to formula (13). TIFF2025512096000012.tif40170, R is in each case the same or different, is an amine radical, in each case an optionally halogenated, preferably fluorohalogenated, more preferably monohalogenated, C1-C8-alkyl radical, preferably a methyl, ethyl, propyl or butyl radical, a C1-C8 alkoxy radical, preferably a methoxy, ethoxy, propoxy or butoxy radical, in each case optionally alkyl-substituted, preferably C1-C4-alkyl-substituted and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C5-C6-cycloalkyl radicals, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine, bromine, and / or hydroxy-substituted, C6-C 20 an aryloxy radical, preferably a phenoxy radical, a naphthyloxy radical, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C7-C 12 - an aralkyl radical, preferably a phenyl-C1-C4-alkyl radical, or a halogen radical, preferably chlorine or fluorine, or is the OH radical, k is a natural number of 1 to 10, preferably 1 to 8, particularly preferably 1 to 5, and especially preferably 1.
[0085] Preferably used herein are commercially available phosphazenes, which are typically ring mixtures of different ring sizes.
[0086] Further preference is given to the following, either individually or in mixtures: propoxyphosphazenes, phenoxyphosphazenes, methylphenoxyphosphazenes, aminophosphazenes, fluoroalkylphosphazenes, and also phosphazenes having the following structure: TIFF2025512096000013.tif125170
[0087] In compounds 13a-13f shown above, k=1, 2, or 3.
[0088] Preferably, the proportion of phosphorus halogen substituted phosphazenes, for example those consisting of incompletely reacted starting materials, is less than 1000 ppm, more preferably less than 500 ppm.
[0089] The phosphazenes can be used alone or in mixtures. The radicals R can always be the same or two or more radicals in the formula can be different. The radicals R of the phosphazenes are preferably identical.
[0090] In one embodiment, only phosphazenes having the same R are used.
[0091] Preferably, the proportion of tetramers (k=2) is, based on component C, 2 mol % to 50 mol %, more preferably 5 mol % to 40 mol %, even more preferably 10 mol % to 30 mol %, particularly preferably 10 mol % to 22 mol %.
[0092] Preferably, the proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) is from 0 mol% to 30 mol%, more preferably from 2.5 mol% to 25 mol%, even more preferably from 5 mol% to 20 mol%, particularly preferably from 6 mol% to 15 mol%, based on component C.
[0093] Preferably, the proportion of oligomers with k≧8 is, based on component C, from 0 mol % to 2.0 mol %, preferably from 0.10 mol % to 1.00 mol %.
[0094] More preferably, the phosphazene of component C satisfies all three above conditions with respect to the proportion of oligomers.
[0095] Particularly preferably, phenoxyphosphazenes (all R=phenoxy, formula 13g) are present as component C, either alone or together with further phosphazenes according to formula (13) as component C, the proportion of oligomers with k=1 (hexaphenoxyphosphazenes) being 50 mol % to 98 mol %, particularly preferably 60% to 72% by weight, based on the amount of phenoxyphosphazene. If phenoxyphosphazenes are used, the proportion of oligomers with k=2 is especially preferably 15% to 22% by weight and those with k≧3 being 10% to 13% by weight. TIFF2025512096000014.tif52170
[0096] Alternatively, component C particularly preferably comprises a phenoxyphosphazene having a proportion of trimers (k=1) of 70 mol% to 85 mol%, a proportion of tetramers (k=2) of 10 mol% to 20 mol%, a proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) of 3 mol% to 8 mol%, and 0.1 mol% to 1 mol% of phosphazene oligomers with k≧8, based on component C, and particularly preferably such a phenoxyphosphazene.
[0097] In an alternative preferred embodiment, n is defined as the arithmetic mean of k, where n is in the range of 1.10 to 1.75, preferably 1.15 to 1.50, more preferably 1.20 to 1.45, and especially preferably 1.20 to 1.40 (including the range limits). TIFF2025512096000015.tif20170
[0098] Phosphazenes and their preparation are described, for example, in EP-A-728811, DE-A-1961668 and WO-A-97 / 40092.
[0099] The oligomer composition in each blend sample was determined after synthesis as follows: 31 Detection and quantification are possible by P NMR (chemical shifts; trimer δ: 6.5 ppm to 10.0 ppm; tetramer δ: -10 ppm to -13.5 ppm; higher oligomers δ: -16.5 ppm to -25.0 ppm).
[0100] Especially preferably, component C comprises a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13), most preferably component C is a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13), very preferably component C is a cyclic phosphazene according to formula (13).
[0101] The content of the phosphorus-containing flame retardant in the composition according to the present invention is 6% by weight to 14% by weight, preferably 7.0% by weight to 12.0% by weight, particularly preferably 8% by weight to 10% by weight, based on the total composition.
[0102] The quotient of the amount of component C, i.e. the phosphorus-containing flame retardant, and the amount of component A, i.e. the aromatic polycarbonate, based on the entire composition, multiplied by 100 is here greater than 10.0, preferably greater than or equal to 10.7, particularly preferably at most 25.
[0103] If the talc content is more than 37% by weight, preferably more than 35.5% by weight, particularly preferably more than 35% by weight, the phosphazene content is more than 10.0% by weight, preferably at least 12% by weight.
[0104] Component D The composition according to the invention contains a fluorine-containing anti-drip agent as component D, which may be a mixture of two or more anti-drip agents. The total amount of anti-drip agents (anti-drip agents) is 0.3% to 2.0% by weight, preferably 0.4% to 1.6% by weight, particularly preferably 0.045% to 1.0% by weight of at least one anti-drip agent.
[0105] The anti-drip agents used are preferably fluorine-containing polymers, especially polyolefins.
[0106] The fluorinated polyolefins preferentially used as anti-drip agents have a high molecular weight, a glass transition temperature above -30°C, generally above 100°C, and a fluorine content preferably between 65% and 76% by weight, in particular between 70% and 76% by weight. Suitable fluorinated polyolefins are polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene / hexafluoropropylene copolymers, and ethylene / tetrafluoroethylene copolymers. Fluorinated polyolefins are known ("Vinyl and Related Polymers" by Schildknecht, John Wiley & Sons, Inc., New York, 1962, pages 484-494; "Fluoropolymers" by Wall, Wiley-Interscience, John Wiley & Sons, Inc., New York, volume 13, 1970, pages 623-654; "Modern Plastics Encyclopedia", 1970-1971, volume 47, No. 10 A, October 1970, McGraw-Hill, Inc., New York, pages 134 and 774; "Modern Plastics Encyclopedia", 1975-1976, October 1975, volume 52, No. 10 A, McGraw-Hill, Inc., New York, pages 27, 28 and (See U.S. Pat. Nos. 3,671,487, 3,723,373, and 3,838,092.) These can be prepared by known methods, for example, in an aqueous medium using a free radical forming catalyst (e.g., sodium peroxodisulfate, potassium peroxodisulfate, or ammonium peroxodisulfate, etc.) at a pressure of 7 kg / cm. 2 ~71kg / cm 2 and polymerizing tetrafluoroethylene at a temperature of 0° C. to 200° C., preferably at a temperature of 20° C. to 100° C. Further details are described, for example, in US Pat. No. 2,393,967.
[0107] Depending on the application, the density of the fluorinated polyolefins is specified according to ISO 1183-1 (2019-09) to be 1.2 g / cm 3 ~2.3g / cm 3 , preferably 2.0 g / cm 3 ~2.3g / cm 3 The average particle size can be between 0.05 μm and 1000 μm as determined using optical microscopy or white light interferometry.
[0108] Suitable tetrafluoroethylene polymer powders are commercially available, for example, from DuPont under the trade name Teflon™.
[0109] Thus, particular preference is given to the use of polytetrafluoroethylene (PTFE), but also in the form of a PTFE-containing composition as the fluorine-containing anti-drip agent. When a PTFE-containing composition is used, its minimum amount is sufficient if the PTFE present in the entire composition is at least 0.2% by weight, preferably at least 0.21% by weight, particularly preferably at least 0.25% by weight. PTFE-containing compositions include Hostaflon™ TF2021 or PTFE blends, such as Blendex™ B449 from Chemtura (approximately 50% by weight of PTFE and approximately 50% by weight of SAN (derived from 80% by weight of styrene and 20% by weight of acrylonitrile)). Particular preference is given to the use of PTFE or a PTFE / SAN blend as the fluorine-containing anti-drip agent.
[0110] Component E Component E of the composition according to the invention is an anhydride-modified α-olefin polymer.
[0111] The α-olefin polymer is preferably based on at least one monomer selected from the group consisting of ethylene, 1-propene, 1-butene, 1-isobutene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-octadecene, 1-nonadecene, but may also be based on a mixture of these monomers. More preferably, the α-olefin polymer is based on at least one monomer selected from the group consisting of ethene, propene, 1-hexene, 1-octene. Particularly preferably, the α-olefin polymer is based on ethylene, propene and / or 1-octene.
[0112] In this context, "based on" means that preferably at least 90 wt. %, more preferably at least 95 wt. %, and especially preferably at least 98 wt. %, of the α-olefin polymers in the polycarbonate-containing composition, based on the total weight of the respective non-anhydride-modified α-olefin polymers, is formed from the respective monomer(s).
[0113] The α-olefin polymers are modified with anhydrides, the modification being carried out using unsaturated carboxylic acid anhydrides, preferably selected from the group consisting of maleic anhydride, phthalic anhydride, fumaric anhydride, itaconic anhydride and mixtures thereof, with particular preference given to maleic anhydride.
[0114] The anhydride modified α-olefin polymers are preferably free of styrene butadiene rubber, especially free of rubber.
[0115] Preferred anhydride modified α-olefin polymers are E1) 90.0% by weight to 99.5% by weight, preferably 92.0% by weight to 97.5% by weight, and more preferably 94.0% by weight to 97.0% by weight of an α-olefin polymer; E2) 0.5% to 10.0% by weight, more preferably 2.5% to 8.0% by weight, and even more preferably 3.0% to 6.0% by weight of an anhydride; Includes.
[0116] The olefin moiety E1) of the α-olefin polymers here is particularly preferably The proportion of ethylene is 65.0% by weight to 96.0% by weight, more preferably 80.0% by weight to 96.0% by weight, and particularly preferably 84.0% by weight to 92.0% by weight; The proportion of propylene is 2.0% by weight to 10.0% by weight, particularly preferably 4.0% by weight to 8.0% by weight, The proportion of 1-octene is 2.0% by weight to 25.0% by weight, more preferably 2.0% by weight to 10.0% by weight, particularly preferably 4.0% by weight to 8.0% by weight; It is characterized by:
[0117] Especially preferably, the α-olefin polymers are not based on any further monomers.
[0118] Alternatively, the olefin portion E1) of the α-olefin polymers is preferably based on propylene and / or ethylene, particularly preferably exclusively on propylene, especially preferably to the extent of at least 98% by weight.
[0119] Average molecular weight M of anhydride-modified α-olefin polymers W is preferably 300 g / mol to 40,000 g / mol, more preferably 800 g / mol to 32,000 g / mol, even more preferably 1,000 g / mol to 22,000 g / mol, and particularly preferably 3,000 g / mol to 21,000 g / mol. W is determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration, where the reported values are preferably average values from duplicate measurements.
[0120] The acid number of the anhydride modified α-olefin polymers is preferably at least 30 mg KOH / g, more preferably 45 mg KOH / g to 170 mg KOH / g, particularly preferably 80 mg KOH / g, as determined by potentiometric titration with alcoholic potassium hydroxide solution in accordance with DIN ISO 17025:2005-08.
[0121] Particularly preferably, the anhydride-modified α-olefin polymers according to component E are based on propene and modified with maleic anhydride, more preferably having an average molecular weight M of 1000 g / mol to 22000 g / mol, even more preferably 3000 g / mol to 21000 g / mol, as determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration. w and an acid number, determined by potentiometric titration according to DIN ISO 17025:2005-08, of 45 mg KOH / g to 170 mg KOH / g, even more preferably of 50 mg KOH / g to 100 mg KOH / g.
[0122] The amount of the anhydride-modified α-olefin polymer in the entire composition is 1 wt% to 3 wt%, preferably 1.2 wt% to 2.5 wt%, more preferably 1.3 wt% to 2.3 wt%, particularly preferably 1.5 wt% to 2 wt%, and especially 2.0 wt%.
[0123] Additional Additives (Component F) The polycarbonate compositions according to the present invention may contain one or more additional additives different from Component B, Component C, Component D, and Component E, which, when present, are collectively referred to as "Component F."
[0124] Other usual additives ("additional additives") are optionally present (0 wt%), preferably up to 10 wt%, even more preferably 0.1 wt% to 5 wt%, particularly preferably 0.1 wt% to 3 wt%, especially preferably 0.2 wt% to 1.0 wt%, these weight percentages being based on the total weight of the composition. The group of additional additives does not include any talc or any phosphorus-containing flame retardant according to component C. The group of additional additives does not include any fluorine-containing anti-drip agent, since this has already been described in component D. The group of additional additives also does not include any anhydride-modified α-olefin polymers according to component E.
[0125] Such further additives, as typically added to polycarbonates, are in particular heat stabilizers, antioxidants, release agents, UV absorbers, IR absorbers, impact modifiers, antistatic agents, flame retardants different from component C, optical brighteners, light scattering agents, hydrolysis stabilizers, transesterification stabilizers, (organic) dyes, (organic / inorganic) pigments, such as titanium dioxide, compatibilizers, and / or laser marking additives, in amounts typical of polycarbonate-based compositions in particular. Such additives are described, for example, in EP-A-0839623, WO-A-96 / 15102, EP-A-0500496 or in "Plastics Additives Handbook", Hans Zweifel, 5th Edition 2000, Hanser Verlag, Munich. Such additives, which can be added individually or else as mixtures, are preferred additives according to the invention.
[0126] If additional additives are present after all, further preferred as additional additives are one or more additional additives selected from the group consisting of heat stabilizers, antioxidants, mold release agents, organic dyes, organic pigments, inorganic pigments, very preferably no additional additives are present. In this case, the proportion of additional additives is particularly preferably 0% to 3% by weight. Particularly preferred as additional additives are at least one heat stabilizer, antioxidant and / or mold release agent, particularly preferably a heat stabilizer.
[0127] It will be understood that such additives can only be added in such amounts if they do not significantly negatively affect the effect according to the invention of high CTI and good flame retardancy, and preferably also do not reduce the Vicat temperature, as specified according to ISO 306:2014-3, VST method B, to below 107° C., preferably below 120° C. It is therefore particularly preferred that in addition to the phosphorus-containing flame retardant according to component C, a further flame retardant is present in an amount of not more than 0.05% by weight. It is especially preferred that no further flame retardant is present at all.
[0128] The composition according to the invention may indeed contain, in addition to component C, further flame retardants, but not those selected from the group of alkali metal, alkaline earth metal or ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide or sulfonimide derivatives, and combinations thereof, "derivatives" being taken to mean compounds having a molecular structure in which, instead of a hydrogen atom or a functional group, a different atom or a different atomic group has been present, or one or more atoms / atom groups have been removed, so that the parent compound is still recognizable.
[0129] Such flame retardants not present in the composition according to the invention are in particular one or more compounds selected from the group consisting of sodium or potassium perfluorobutane sulfate, sodium or potassium perfluoromethanesulfonate, sodium or potassium perfluorooctane sulfate, sodium or potassium 2,5-dichlorobenzenesulfate, sodium or potassium 2,4,5-trichlorobenzenesulfonate, sodium or potassium diphenylsulfonesulfonate, sodium or potassium 2-formylbenzenesulfonate, sodium or potassium (N-benzenesulfonyl)benzenesulfonamide or mixtures thereof, among which particular preference is given to sodium or potassium perfluorobutanesulfate, sodium or potassium perfluorooctane sulfate, sodium or potassium diphenylsulfonesulfonate or mixtures thereof, in particular potassium perfluoro-1-butanesulfonate (which is commercially available, inter alia, as Bayowet® C4 from Lanxess, Leverkusen, Germany).
[0130] Additives which are particularly preferably present are release agents, more preferably release agents based on fatty acid esters, even more preferably release agents based on stearic acid esters, very preferably release agents based on pentaerythritol. Particular preference is given to the use of pentaerythritol tetrastearate (PETS) and / or glycerol monostearate (GMS). If one or more release agents are used, their amount is preferably up to 1.0% by weight (inclusive), more preferably 0.01% to 0.7% by weight, particularly preferably 0.02% to 0.60% by weight, each based on the total composition.
[0131] An additive which is also particularly preferably present is a heat stabilizer, the amount of which is preferably up to 0.20% by weight, more preferably 0.01% to 0.10% by weight, even more preferably 0.01% to 0.05% by weight, particularly preferably 0.015% to 0.040% by weight, based on the total composition.
[0132] Suitable heat stabilizers are especially phosphorus-based stabilizers selected from the group of phosphates, phosphites, phosphonites, phosphines, and mixtures thereof.Examples include triphenyl phosphite, alkyl diphenyl phosphite, dialkyl phenyl phosphite, tris(nonylphenyl) phosphite, trilauryl phosphite, trioctadecyl phosphite, distearyl pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite (Irgafos® 168), diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite (Do verphos(trademark) S-9228), bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, diisodecyloxypentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tris(tert-butylphenyl)pentaerythritol diphosphite, tristearyl sorbitol triphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, 6-isooctyl peroxy-2,4,8,10-tetra-tert-butyl-12H-dibenzo[d,g]-1,3,2-dioxaphosphocin, bis(2,4-di-tert-butyl-6-methylphenyl)methyl phosphite, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyldibenzo[d,g]-1,3,2-dioxaphosphocin, 2,2',2''-nitrilo[triethyltris(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl 2-ethylhexyl (3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl) phosphite, 5-butyl-5-ethyl-2-(2,4,6-tri-tert-butylphenoxy)-1,3,2-dioxaphosphiran, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, triphenylphosphine (TPP), trialkylphenylphosphine, bisdiphenylphosphinoethane, or trinaphthylphosphine.These can be used alone or in mixtures, for example Irganox® B900 (a mixture of Irgafos® 168 and Irganox® 1076 in a ratio of 4:1) or a mixture of Doverphos® S-9228 with Irganox® B900 or Irganox® 1076. Particularly preferably, triphenylphosphine (TPP), Irgafos® 168 or tris(nonylphenyl)phosphite or mixtures thereof are used.
[0133] It is also possible to use phenolic antioxidants, such as alkylated monophenols, alkylated thioalkylphenols, hydroquinones and alkylated hydroquinones.Particular preference is given to using Irganox® 1010 (pentaerythritol 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; CAS: 6683-19-8) and Irganox® 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), preferably in an amount of 0.05% to 0.5% by weight.
[0134] It is also possible to add sulfonates or alkyl phosphates, such as mono-, di-, and / or trihexyl phosphate, triisooctyl phosphate, and / or trinonyl phosphate, as transesterification inhibitors. The alkyl phosphate used is preferably triisooctyl phosphate (tris-2-ethylhexyl phosphate). It is also possible to use mixtures of various mono-, di-, and / or trialkyl phosphates. Triisooctyl phosphate is preferably used in an amount of 0.003% to 0.05% by weight, more preferably 0.005% to 0.04% by weight, particularly preferably 0.01% to 0.03% by weight, based on the total composition.
[0135] Examples of impact modifiers are: core-shell polymers, such as ABS or MBS; olefin-acrylate copolymers, such as the Elvaloy™ variety from DuPont or the Paraloid™ variety from Dow; silicone acrylate rubbers, such as the Metablen™ variety from Mitsubishi Rayon Co., Ltd. The composition according to the present invention already has an exceptional property profile without additional impact modifiers. Therefore, the composition according to the present invention preferably does not contain impact modifiers.
[0136] Particularly preferably, the composition according to the invention does not contain, in addition to talc, any further fillers, such as barium sulfate, etc. Titanium dioxide is not considered here as a "filler", but rather as a white pigment.
[0137] The polymer composition according to the invention, which contains in admixture component A, component B, component C, component D, component E and optionally component F, and optionally also further constituents, can be prepared using a powder premix. It is also possible to use a premix of pellet materials or pellet materials and powders together with the additives according to the invention. It is also possible to use a premix formed from a solution of the mixture of components in a suitable solvent, optionally followed by homogenization of the solution and removal of the solvent. In particular, the additives and further constituents, referred to as component F of the composition according to the invention, can also be introduced by known methods or in the form of a masterbatch. The use of masterbatches is particularly suitable for the introduction of the additives and further constituents, and masterbatches based on the respective polymer matrix are particularly used.
[0138] The composition according to the invention can be extruded, for example. After extrusion, the extrudate can be cooled and crushed. The premix can also be mixed together in the melt in the plasticizing unit of an injection molding machine. In this case, the melt is directly converted into a molded article in a subsequent step.
[0139] The compositions according to the invention are preferably used to manufacture moldings for components of the EE sector, in particular for high voltage switches, inverters, relays, electronic connectors, electrical connectors, circuit breakers, components for photovoltaic applications, electric motors, heat sinks, chargers and charging plugs for electric vehicles, electrical junction boxes, smart meter housings, miniature circuit breakers, busbars. The invention therefore also provides moldings which are part of the corresponding EE components. A "component" may be an individual element of a complex product, but also the entire element.
[0140] The invention therefore also provides moldings which consist of the composition according to the invention or which comprise a region made of the composition according to the invention, as well as corresponding parts which comprise an element or molding which consists of the composition according to the invention or which comprise a region made of the composition according to the invention.
[0141] Moldings in the sense of the present invention are also insulating layers made of the compositions according to the present invention. Such layers can be provided, for example, on inverters as layers that protect against external influences. For inverters, standard insulating materials have a CTI of 600V. The compositions according to the present invention can also be used as insulating layers for other electrical components, for example transistors. The insulating layer provides a reliable separation, for example, between the transistor and the metal heat sink.
[0142] Mouldings consisting of the thermoplastic composition according to the invention or comprising areas made of the thermoplastic composition according to the invention, or layers of the thermoplastic composition according to the invention, are preferably used in EE components designed for a working voltage of at least 375 V, preferably at least 400 V. However, they can also be designed for 230 V±23 V, which is the typical European domestic working voltage, although a reduction in the conductor distance can be achieved here.
[0143] The high comparative tracking index of the polycarbonate composition according to the invention makes it possible to use this polycarbonate material to reduce the distance between two conductors in a component than was previously possible using polycarbonate.
[0144] Accordingly, the present invention also provides an EE component, comprising a first conductor and a second conductor at a first distance d1 and a second distance d2 relative to each other, These electrical conductors are connected via an element made of a thermoplastic composition according to the invention, which is in direct contact with the first electrical conductor and the second electrical conductor, distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected to prevent sparks through the air at each operating voltage; d1 is as follows, at the working voltage U listed below: d1i(0V≦U≦250V):1.8mm~<2.5mm d1ii(250V <U≦500V)=3.6mm~<5.0mm d1iii(500V <U≦1000V)=7.1mm~<10.0mm。
[0145] Such short distances are only achievable using materials with a CTI of at least 400V.
[0146] "Element made of a thermoplastic composition according to the invention" means in this specification that an element is present that consists of a thermoplastic composition according to the invention, i.e. the composition has not been mixed with additional components.
[0147] Even shorter distances are achievable if the CTI of the material is 600V, for example, in which case d1 is preferably as follows at the recited working voltages: d1i(0V≦U≦250V):1.3mm~<2.5mm, d1ii(250V <U≦500V)=2.5mm~<5.0mm、 d1iii(500V <U≦1000V)=5.0mm~<10.0mm。
[0148] When using a material with a CTI of 600 V, d1 is particularly preferably as follows at the listed operating voltages: d1i(0V≦U≦250V): 1.3 mm to <1.8 mm, d1ii(250V < U≦500V) = 2.5 mm to <3.6 mm, d1iii(500V < U≦1000V) = 5.0 mm to <7.1 mm. These distances cannot be achieved even if a material with a CTI of 400 V or 450 V is used, and a CTI of 600 V is required.
[0149] Accordingly, the present invention also provides corresponding EE components in which the corresponding distances are achieved, preferably with an operating voltage of at least 375 V, preferably at least 400 V, and particularly preferably at least 600 V applied.
[0150] The selection of d2 is within the ability of those skilled in the art. Preferably, d2 is at least 1.2 mm.
[0151] The present invention also provides the use of the composition according to the present invention to achieve the above-mentioned short distances between conductors in EE components, even in the embodiments described as preferred, particularly preferred, etc.
[0152] The present invention further provides the use of the composition according to the present invention to achieve a CTI of at least 400 V, preferably at least 600 V, more preferably in combination with an in-plane thermal conductivity of at least 0.9 W / (mK) specified in accordance with ASTM E 1461-13. It will be understood that the embodiments of the composition according to the present invention referred to as preferred, more preferred, particularly preferred, etc. are also applicable to the use according to the present invention.
[0153] It is known that the degree of contamination affects conductivity. The distances d1 and d2 mentioned are practical, for example, in components that comply with the IP6K9K protection degree according to ISO 20653:2013-02 due to structural shielding.
[0154] Preferred thermoplastic compositions according to the invention belong to insulating material group II (400V≦CTI<600V), particularly preferred compositions belong to insulating material group I (600V≦CTI), classified according to DIN EN 60664-1:2008.
[0155] They preferably have a thermal conductivity (in-plane) of at least 0.9 W / (mK), as specified according to ASTM E 1461-13, so that good heat dissipation can further be achieved.
[0156] Various embodiments of the present invention are described below:
[0157] 1. A thermoplastic composition comprising: A) at least 44.5% by weight of an aromatic polycarbonate; Here, the aromatic polycarbonate is Contains one or more monomer units of formula (1a) in a proportion of 30% by weight to 65% by weight based on the total weight of the aromatic polycarbonate; TIFF2025512096000016.tif44170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, R 2 is a C1-C4-alkyl radical, n is 0, 1, 2, or 3; B) 30% to 40% by weight of talc; C) 6% by weight to 14% by weight of a phosphorus-containing flame retardant; where the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3% by weight to 2.0% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; Contains When the talc content is less than 35.0% by weight, the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight; A thermoplastic composition, wherein when the talc content is greater than 37 wt.%, the phosphazene content is greater than 10.0 wt.%.
[0158] 2. The thermoplastic composition according to embodiment 1, in which the proportion of monomer units of formula (1a), based on the total weight of the aromatic polycarbonate, is between 40% and 60% by weight, in particular between 40% and 50% by weight.
[0159] 3. The thermoplastic composition according to embodiment 1 or 2, wherein the talc content of the thermoplastic composition is 30% to 35% by weight.
[0160] 4. The thermoplastic composition according to any of the previous embodiments, wherein the amount of the fluorine-containing anti-drip agent is 0.4 wt.% to 1.0 wt.%.
[0161] 5. A thermoplastic composition according to any of the previous embodiments, wherein the amount of aromatic polycarbonate is at least 50% by weight.
[0162] 6. The thermoplastic composition according to any of the first or third to fifth embodiments, wherein the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is up to 60% by weight based on the total weight of the aromatic polycarbonate.
[0163] 7. A thermoplastic composition according to any of the previous embodiments, wherein the phosphorus-containing flame retardant is a phosphazene or a mixture of different phosphazenes.
[0164] 8. A thermoplastic composition according to any of the previous embodiments, wherein the anhydride-modified α-olefin polymer comprises a maleic anhydride-modified propylene polymer.
[0165] 9. A thermoplastic composition according to any of the previous embodiments, wherein the composition contains 0.2% to 2.0% by weight of titanium dioxide.
[0166] 10. A thermoplastic composition according to any of the previous embodiments, wherein the proportion of monomeric units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 40% by weight when the talc content is less than 35% by weight.
[0167] 11. A thermoplastic composition according to any of the previous embodiments, wherein the quotient of the amount of component C based on the entire composition and the amount of component A based on the entire composition multiplied by 100 is 10.7 or greater.
[0168] 12. A thermoplastic composition according to any of the previous embodiments, wherein the quotient of the amount of component C based on the entire composition and the amount of component A based on the entire composition multiplied by 100 is 25 or less.
[0169] 13. A thermoplastic composition according to any of the previous embodiments, wherein when the talc content is greater than 35.5 wt.%, the phosphazene content is greater than 10.0 wt.%, preferably at least 12 wt.%.
[0170] 14. A) at least 50% by weight of an aromatic polycarbonate; Here, the aromatic polycarbonate is Contains one or more monomer units of formula (1a) in a proportion of 30% by weight to 65% by weight, preferably 60% by weight, based on the total weight of the aromatic polycarbonate; TIFF2025512096000017.tif45170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, R 2 is a C1-C4-alkyl radical, n is 0, 1, 2, or 3; B) 30% to 35% by weight of talc; C) 6% by weight to 12% by weight of a phosphorus-containing flame retardant; where the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3% by weight to 2.0% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; Contains The thermoplastic composition according to any of the previous embodiments, wherein the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight, preferably at least 40% by weight, if the talc content is less than 35.0% by weight.
[0171] 15. The thermoplastic composition according to embodiment 14, wherein the proportion of the monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is 35% by weight to 45% by weight, and the amount of the phosphorus-containing flame retardant is 8% by weight to 10% by weight.
[0172] 16. A) at least 44.5% by weight of an aromatic polycarbonate; Here, the aromatic polycarbonate is Contains one or more monomer units of formula (1a) in a proportion of 30% by weight to 65% by weight based on the total weight of the aromatic polycarbonate; TIFF2025512096000018.tif46170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, R 2 is a C1-C4-alkyl radical, n is 0, 1, 2, or 3; B) 30% to 40% by weight of talc; C) 6% by weight to 14% by weight of a phosphorus-containing flame retardant; where the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3% by weight to 2.0% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; F) optionally, one or more additional additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, flame retardants different from component C, fluorescent whitening agents, light scattering agents, hydrolysis stabilizers, transesterification stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; It consists of: When the talc content is less than 35.0% by weight, the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight; 14. The thermoplastic composition according to any of the preceding embodiments, wherein the phosphazene content is greater than 10.0 wt.% when the talc content is greater than 37 wt.%.
[0173] 17. A thermoplastic composition according to any of the previous embodiments, wherein the phosphorus-containing flame retardant comprises a cyclic phosphazene and / or a phosphorus compound of formula (10).
[0174] 18. The phosphorus-containing flame retardant is a cyclic phosphazene and / or a phosphorus compound of formula (10), TIFF2025512096000019.tif35170 formula, R 1 , R 2 , R 3 , and R 4 are independently a C1-C8-alkyl radical, which in each case is optionally halogenated, in each case branched or unbranched, and / or a C5-C6-cycloalkyl radical, a C6-C 20 -aryl radical, or C7-C 12 - aralkyl radicals, which in each case are optionally substituted by branched or unbranched alkyl and / or halogen, preferably chlorine and / or bromine, n is independently 0 or 1; q is a value between 0 and 30; A thermoplastic composition according to any of the previous embodiments, wherein X is a monocyclic or polycyclic aromatic radical having 6 to 30 carbon atoms, or a linear or branched chain aliphatic radical having 2 to 30 carbon atoms, each of which can be substituted or unsubstituted and can be crosslinked or non-crosslinked.
[0175] 19. The cyclic phosphazene is a phosphazene of formula (13): TIFF2025512096000020.tif40170 formula, R is in each case the same or different, is an amine radical, in each case an optionally halogenated, preferably fluorohalogenated, more preferably monohalogenated, C1-C8-alkyl radical, preferably a methyl, ethyl, propyl or butyl radical, a C1-C8 alkoxy radical, preferably a methoxy, ethoxy, propoxy or butoxy radical, in each case optionally alkyl-substituted, preferably C1-C4-alkyl-substituted and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C5-C6-cycloalkyl radicals, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine, bromine, and / or hydroxy-substituted, C6-C 20 an aryloxy radical, preferably a phenoxy radical, a naphthyloxy radical, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C7-C 12 - an aralkyl radical, preferably a phenyl-C1-C4-alkyl radical, or a halogen radical, preferably chlorine or fluorine, or is the OH radical, The thermoplastic composition according to embodiment 17 or 18, wherein k is a natural number from 1 to 10, preferably from 1 to 8, particularly preferably from 1 to 5, and especially preferably 1.
[0176] 20. The phosphorus compound of formula (10) is a bisphenol A-based oligophosphate ester of formula (12), TIFF2025512096000021.tif54170The thermoplastic composition according to embodiment 17, 18 or 19, wherein q=1 to 20, in particular q=1.0 to 1.2.
[0177] 21. The anhydride-modified α-olefin polymers according to component E are based on propene and modified with maleic anhydride, preferably having an average molecular weight M of 1000 g / mol to 22000 g / mol, preferably 3000 g / mol to 21000 g / mol, as determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration. w and an acid number, determined by potentiometric titration according to DIN ISO 17025:2005-08, of 45 mg KOH / g to 170 mg KOH / g, preferably of 50 mg KOH / g to 100 mg KOH / g.
[0178] 22. The monomer unit of formula (1a) is R 1 is hydrogen and R 2 A thermoplastic composition according to any of the previous embodiments, wherein is a methyl radical and n is 3.
[0179] 23. A thermoplastic composition according to any of the previous embodiments, wherein the aromatic polycarbonate is or includes APEC™.
[0180] 24. The aromatic polycarbonate contains 40% by weight to 55% by weight, in particular 50% by weight, of one or more monomer units of formula (1a), based on the total weight of the aromatic polycarbonate; TIFF2025512096000022.tif46170 formula, R 1 is hydrogen or a C1-C4-alkyl radical, R 2 is a C1-C4-alkyl radical, The thermoplastic composition according to any of the previous embodiments, wherein n is 0, 1, 2, or 3.
[0181] 25. A molding comprising a region made of or from a thermoplastic composition according to any of the previous embodiments.
[0182] 26. The molding according to embodiment 25, wherein the molding is part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a photovoltaic power generation system, an electric motor, a heat sink, an electric vehicle charger or charging plug, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.
[0183] 27. An EE part designed for a working voltage of at least 375 V, comprising a layer made of a molding according to embodiment 25 or 26, or a thermoplastic composition according to any of embodiments 1 to 24.
[0184] 28. An EE part designed for a working voltage of 400 V, comprising a layer made of a molding according to embodiment 24 or 25, or a thermoplastic composition according to any of embodiments 1 to 24.
[0185] 29. An EE part, a first conductor and a second conductor at a first distance d1 and a second distance d2 from each other; Including, They are connected via an element made of a thermoplastic composition according to any one of embodiments 1 to 24, the element being in direct contact with the first electrical conductor and the second electrical conductor; distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected such that a spark through air is prevented at each operating voltage. d1, at the operating voltages U listed below: d1i (0V ≤ U ≤ 250V): 1.8 mm to <2.5 mm d1ii (250V < U ≤ 500V) = 3.6 mm to <5.0 mm d1iii (500V < U ≤ 1000V) = 7.1 mm to <10.0 mm is an EE component.
[0186] 30. An EE component, including a first conductor and a second conductor that are at a first distance d1 and a second distance d2 from each other, wherein they are connected via an element made of a thermoplastic composition according to any of Embodiments 1 to 24, and this element is in direct contact with the first conductor and the second conductor, the distance d1 is the shortest distance between the first conductor and the second conductor along the surface of the element made of the thermoplastic composition, the distance d2 is the shortest distance between the first conductor and the second conductor through air, d2 is selected such that a spark through air is prevented at each operating voltage, Preferably according to either of Embodiments 27 and 28, d1, at the operating voltages U listed below, is as follows: d1i (0V ≤ U ≤ 250V): 1.3 mm to <2.5 mm, preferably <1.8 mm, d1ii (250V < U ≤ 500V) = 2.5 mm to <5.0 mm, preferably <3.6 mm, d1iii (500V < U ≤ 1000V) = 5.0 mm to <10.0 mm, preferably <7.1 mm.
[0187] 31. An EE component according to any of Embodiments 27 to 30, wherein d2 is 1.2 mm or more.
[0188] 32. The EE component according to any of embodiments 27 to 31, which is a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, part of a solar power generation system, part of an electric motor, part of a heat sink, part of a charger and a charging plug for an electric vehicle, part of an electrical junction box, part of a smart meter housing, part of a miniature circuit breaker, or part of a busbar.
[0189] 33. An EE part according to any of embodiments 27 to 32, having an IP6K9K degree of protection according to ISO 20653:2013-02. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0190] 1. Description of raw materials and testing methods a) Raw materials Component A-1: A linear polycarbonate based on bisphenol A, which has a melt volume flow rate of 12 cm 3 / (10 min) (in accordance with ISO 1133:2012-03 at a test temperature of 300° C. and a load of 1.2 kg) and contains 250 ppm (=0.025% by weight, based on the total weight of component A) of triphenylphosphine heat stabilizer as component F-2.
[0191] Component A-2: A linear copolycarbonate based on bisphenol A and bisphenol TMC (66% by weight), which is 8 cm 3 It has an MVR of 330°C / 2.16 kg (ISO 1133-1:2011) of 10 min and a softening temperature of 203°C (VST / B 120; ISO 306:2013).
[0192] Component A-3: A linear copolycarbonate based on bisphenol A and bisphenol TMC (13% by weight), which is 45 cm 3 It has an MVR of 330°C / 2.16 kg (ISO 1133-1:2011) of 10 min and a softening temperature of 158°C (VST / B 120; ISO 306:2013).
[0193] Component B-1: Compressed talc, which has a talc content of 98% by weight, an iron oxide content of 1.9% by weight, an aluminum oxide content of 0.2% by weight, an ignition loss of 5.4% by weight (DIN 51081 / 1000°C), a pH of 9.15 (according to EN ISO 787-9:1995), a D(0.5) of 2.2 μm (sedimentation analysis), a viscosity of 10 m 2 / g BET surface area according to ISO 4652:2012-06, trade name: Finntalc M05SLC, manufacturer: Mondo Minerals BV.
[0194] Component B * -2: Glass fiber from Nitto Boseki Co., Ltd. (2-4-1 Kojimachi, Chiyoda-ku, Tokyo 102-8489, Japan) available under the trade name CSG 3PA-830. This is a flat glass fiber with a cut length of 3 mm and a cross-sectional area ratio of 1.4.
[0195] Component B * -3: Amosil FW 600 calcined silicon dioxide from Quarzwerke GmbH, Frechen, which is unsized and has an average particle size D(0.5) of about 4 μm, a D(0.98) of about 13 μm, a D(0.1) / D(0.9) ratio of about 1.5 / 10, and a pore size (pore diameter) of about 6 μm as specified according to DIN-ISO 9277:2014-01. 2 / g.
[0196] Component C-1: Rabitle FP110 phenoxycyclophosphazene, manufactured by Fushimi Pharmaceutical Co., Ltd. (Japan), has the formula (13g) and the trimer content (k=1) is approximately 68 mol%.
[0197] Component D-1: ADS5000 SAN encapsulated polytetrafluoroethylene (approximately 50% by weight PTFE (a fluorine-containing anti-drip agent) and approximately 50% by weight SAN), manufactured by Chemical Innovation Co., Ltd. Thailand.
[0198] Component E-1: Propylene-maleic anhydride polymer, which has an average molecular weight (gel permeation chromatography in orthodichlorobenzene with polystyrene calibration at 150° C.) Mw=20700 g / mol, Mn=1460 g / mol, acid number determined by potentiometric titration according to DIN ISO 17025:2005-08 of 78 mg KOH / g.
[0199] Ingredient F-1: Titanium dioxide from Kronos, which is D 50 = 210 nm (scanning electron microscopy, ECD method; Kronos™ 2230).
[0200] Bisphenol TMC content ("TMC%") indicates the proportion (in weight percent) of bisphenol TMC as a monomer unit in the aromatic polycarbonate.
[0201] b) Test method Comparative Tracking Index (CTI): For the purpose of determining the comparative tracking index, the compositions described herein were tested according to the rapid test method according to IEC 60112:2009. For this purpose, a 0.1% ammonium chloride test solution (395 ohm·cm resistivity) was dropped onto the surface of a test specimen with dimensions 60 mm×40 mm×4 mm, between two adjacent electrodes spaced 4 mm apart, with a time interval of 30 seconds. A test voltage was applied between the electrodes and varied over the course of the test. The first test specimen was tested with a starting voltage of 300 V or 350 V. A maximum of 50 drops in total per voltage (one drop every 30 seconds) were dropped as long as no tracking current of more than 0.5 A occurred for 2 seconds or the specimen did not burn. After 50 drops, the voltage was increased by 50 V and a new specimen was tested at this increased voltage according to the procedure described above. This process continued until either 600 V was reached or a tracking current or burning occurred. If any of the above effects occurred already in less than 50 drops, the voltage was reduced by 25V and a new specimen was tested at this reduced voltage. The voltage was reduced until the test completed 50 drops without causing tracking current or burning. Thus, this procedure was used to identify the maximum possible voltage at which the composition could withstand 50 drops of test solution without causing tracking current. Finally, for confirmation, four more specimens were tested with 50 drops each at the maximum voltage specified. This confirmed value was reported as the CTI in the examples. The 100 drop value was not specified because it was a "rapid test method based on" the specified standard.
[0202] Flame Retardant: The flame retardancy of the polycarbonate compositions was tested at thicknesses of 1.5 mm to 3 mm according to Underwriters Laboratories method UL 94 V. The tested test bars were preconditioned at 50% relative humidity and 70° C. ambient temperature for 7 days.
[0203] Depending on the behavior of the specimens, they are assigned to various flammability classes, including time to flame extinguish, drip resistance, or whether the material produces flammable drips. Hereinafter, the identified classes will be designated V0, V1, and V2. These are established based on a total of five specimens tested.
[0204] V0: A specimen that, when placed at 180° (perpendicular) with its long axis to the flame, has an average afterflame time of 10 seconds or less after the flame is removed and does not produce any drips of plastic particles that ignite cotton wool placed under the specimen. The total afterflame time with two applications of the flame to each of the five specimens is a maximum of 50 seconds.
[0205] V1: In contrast to V0, the average maximum afterflame time in this case is less than 30 seconds, but again no ignition of dripping particles or cotton wool is permitted. The total afterflame time with two flame applications to each of the five specimens is less than 250 seconds.
[0206] V2: In contrast to V0 and V1, this classification results in the formation of drips of plastic particles which ignite the cotton wool. The individual afterflame times are less than 30 seconds and the total afterflame time of two flame applications to each of the five specimens is less than 250 seconds.
[0207] f: If the afterflame time exceeds the above, this test does not assign a flame retardant classification.
[0208] FOT: Flame out time (afterflame time), reported in seconds.
[0209] Heat Distortion Resistance: The heat distortion resistance of the compositions was determined on test specimens with dimensions 80 mm x 10 mm x 4 mm based on the Vicat softening temperature (Method B, test force 50 N, heating rate 50 K / h) according to ISO 306:2014-3.
[0210] Thermal Conductivity: Thermal conductivity is measured according to ASTM E 1461-13 (Nano Flash method) for a 60 x 60 x 2 mm 3 The material was determined on injection molded specimens of 100 mm diameter. "In-plane" means measurements in the x and y directions.
[0211] 2. Preparation of Test Specimens The compositions were prepared in a BUSS kneader. Melt temperature, rotation speed, throughput and torque had to be adjusted for each composition, according to procedures known to those skilled in the art. Fillers were generally metered in through a side extruder. Test pieces with dimensions 60 mm x 40 mm x 4 mm were produced from the molding compounds using standard injection molding techniques, with a melt temperature of 280°C and a mold temperature of 80°C.
[0212] 3.Results In the table below, "nt" means "not tested" and "f" means "failed."
[0213] As shown in Table 1, increasing the bisphenol TMC content has only a minimal positive effect on the CTI but leads to a deterioration in flame retardancy, especially as evidenced by the afterflame time which is significantly longer than that of the pure homopolycarbonate (V-1). Thermal conductivity decreases only slightly with increasing bisphenol TMC content in the range tested.
[0214] [Table 1]
[0215] Table 2 includes compositions with 30% by weight of talc and 6% to 7% by weight of phosphazene and shows the effect of different contents of bisphenol TMC on the Vicat temperature, flame retardant properties and CTI. "FR corr." is the corrected flame retardant content of the composition (component C). It is the quotient of the amount of phosphazene and the amount of aromatic polycarbonate multiplied by 100. As already shown in table 1, the bisphenol TMC content without added flame retardant has a small positive effect on the CTI, but as the value increases, the Vicat softening temperature increases, which is essential for a balanced profile of properties. With the addition of flame retardant, a somewhat larger positive effect of the TMC content on the CTI can surprisingly be seen. For example, the composition without TMC (V-9) has a CTI of only 275V, which can be increased to 325V-350V (V-10, V-11) with 10wt%-20wt% bisphenol TMC and up to 400V (E-12, E-13) with 40wt%-50wt% bisphenol TMC based on aromatic polycarbonate.
[0216] As expected, the Vicat heat distortion resistance increases, the afterflame time increases, and the flame retardancy decreases with increasing bisphenol TMC content.
[0217] [Table 2]
[0218] Table 3 includes compositions based on aromatic polycarbonate with 30% by weight of talc and 40% by weight of bisphenol TMC monomer units and different contents of phosphazene to show the effect of the flame retardant on the burning behavior and the CTI and Vicat temperature. As the examples (V-9 to V-21 in Table 3) show, there is a correlation between the amount of flame retardant, the amount of talc and the TMC content, as a consequence of which the flame retardant class V-0 required at least at 2 mm can only be achieved within a certain range, and the Vicat temperature of the target composition must be as high as possible. The Vicat softening temperature decreases continuously with increasing phosphazene content, reaching a value of 132°C for the optimal composition in terms of flame retardancy and CTI (E-18). Comparing this composition with (V-9), the advantageous use of TMC in combination with phosphazene becomes evident, both in terms of Vicat temperature and CTI. The thermal conductivity of all compositions is in the desired range of 0.9 W / (m·K) to 1.1 W / (m·K).
[0219] In contrast to the talc-filled compositions, the use of large amounts of glass fiber (V-20) or quartz (V-21), also in combination with phosphazenes, does not positively affect the CTI or significantly improve thermal conductivity compared to unfilled polycarbonate.
[0220] [Table 3]
[0221] Compositions consisting of polycarbonate with 35% and 40% by weight of talc and different TMC contents are summarized in Table 4. It can also be seen that the talc content, TMC concentration and amount of flame retardant are interrelated, and both high CTI and good flame retardancy can be achieved only within a certain range. By slightly increasing the concentration of MAH-modified polymer, the CTI also increases further (E-24 and E-25).
[0222] The higher the talc content, the lower the flame retardancy, which is evident from the long after-flame time. This phenomenon can only be compensated for by increasing the amount of flame retardant (reduced after-flame time). However, the Vicat softening temperature decreases with increasing flame retardant content, so that in order to maintain a still sufficiently high Vicat softening temperature of at least 120°C, it is necessary to modify the bisphenol TMC content of the composition (V-28 and V-32).
[0223] [Table 4]
Claims
1. 1. A thermoplastic composition comprising: A) at least 44.5% by weight of an aromatic polycarbonate; Here, the aromatic polycarbonate is Contains one or more monomer units of formula (1a) in a proportion of 30% by weight to 65% by weight based on the total weight of the aromatic polycarbonate; During the ceremony, R 1 is hydrogen or C 1 ~C 4 is an alkyl radical, R 2 is C 1 ~C 4 - is an alkyl radical, n is 0, 1, 2, or 3; B) 30% to 40% by weight of talc; C) 6% to 14% by weight of a phosphorus-containing flame retardant; wherein the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3 wt.% to 2.0 wt.% of a fluorine-containing anti-drip agent; E) 1 wt % to 3 wt % of an anhydride modified α-olefin polymer; Contains When the talc content is less than 35.0% by weight, the proportion of the monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight; A thermoplastic composition, wherein when the talc content is greater than 37 wt.%, a phosphazene is present as a phosphorus-containing flame retardant, and the phosphazene content is greater than 10.0 wt.%, based on the total composition.
2. 2. The thermoplastic composition according to claim 1, wherein the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is from 40% by weight to 60% by weight.
3. The thermoplastic composition according to claim 1 or 2, wherein the talc content of the thermoplastic composition is from 30% to 35% by weight.
4. The thermoplastic composition according to any one of claims 1 to 3, wherein the amount of the fluorine-containing anti-drip agent is from 0.4% to 1.0% by weight.
5. The thermoplastic composition according to any one of claims 1 to 4, wherein the phosphorus-containing flame retardant is a phosphazene or a mixture of different phosphazenes.
6. The thermoplastic composition of any one of claims 1 to 5, wherein the anhydride modified α-olefin polymer comprises a maleic anhydride modified propylene polymer.
7. The thermoplastic composition according to any one of claims 1 to 6, wherein the composition contains from 0.2% to 2.0% by weight of titanium dioxide.
8. 8. The thermoplastic composition according to claim 1, wherein the proportion of monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 40% by weight when the talc content is less than 35% by weight.
9. The thermoplastic composition according to any one of claims 1 to 8, wherein the quotient of the amount of component C based on the entire composition and the amount of component A based on the entire composition multiplied by 100 is 10.7 or more.
10. The thermoplastic composition according to any one of claims 1 to 9, A) at least 50% by weight of an aromatic polycarbonate; wherein the proportion of the monomer unit of formula (1a) based on the total weight of the aromatic polycarbonate is 30% by weight to 60% by weight; B) 30% to 35% by weight of talc; C) 6% to 12% by weight of a phosphorus-containing flame retardant; wherein the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3 wt.% to 2.0 wt.% of a fluorine-containing anti-drip agent; E) 1 wt % to 3 wt % of an anhydride modified α-olefin polymer; Contains A thermoplastic composition, wherein when the talc content is less than 35.0 wt.%, the proportion of monomer units of formula (1a) is at least 35 wt.%, based on the total weight of said aromatic polycarbonate.
11. The thermoplastic composition according to any one of claims 1 to 9, A) at least 44.5% by weight of an aromatic polycarbonate; wherein the proportion of the monomer unit of formula (1a) based on the total weight of the aromatic polycarbonate is 30% by weight to 65% by weight; B) 30% to 40% by weight of talc; C) 6% to 14% by weight of a phosphorus-containing flame retardant; wherein the amount of component C based on the entire composition; The quotient of the amount of component A based on the entire composition and multiplied by 100 is is greater than 10.0; D) 0.3 wt.% to 2.0 wt.% of a fluorine-containing anti-drip agent; E) 1 wt % to 3 wt % of an anhydride modified α-olefin polymer; F) optionally, one or more additional additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, impact modifiers, antistatic agents, flame retardants different from component C, fluorescent whitening agents, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; It consists of: When the talc content is less than 35.0% by weight, the proportion of the monomer units of formula (1a) based on the total weight of the aromatic polycarbonate is at least 35% by weight; A thermoplastic composition, wherein when the talc content is greater than 37 wt.%, a phosphazene is present as a phosphorus-containing flame retardant, and the phosphazene content is greater than 10.0 wt.%, based on the total composition.
12. A moulded article consisting of or comprising a region made of the thermoplastic composition according to any one of claims 1 to 11.
13. 13. The molding of claim 12, wherein the molding is a part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a solar power system, an electric motor, a heat sink, an electric vehicle charger and charging plug, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.
14. An EE part, a first conductor and a second conductor at a first distance d1 and a second distance d2 from each other; Including, They are connected via the thermoplastic composition according to any one of claims 1 to 11, the thermoplastic composition being in direct contact with the first electrical conductor and the second electrical conductor; the distance d1 is the shortest distance between the first electrical conductor and the second electrical conductor along a surface of the thermoplastic composition; the distance d2 is the shortest distance between the first conductor and the second conductor through air, d2 is selected to prevent sparks through the air at each operating voltage; d1 is, at the working voltage U listed below, d1i (0V≦U≦250V): 1.8mm~<2.5mm d1ii (250V<U≦500V)=3.6mm~<5.0mm d1iii (500V<U≦1000V)=7.1mm~<10.0mm That is, EE parts.
15. EE part according to claim 14, having a degree of protection IP6K9K according to ISO 20653:2013-02.
Citation Information
Patent Citations
Polycarbonate composition comprising talc
WO2018037037A1